CasRx-mediated RNA targeting prevents choroidal neovascularization in a mouse model of age-related macular degeneration. Issue 5 (3rd March 2020) - Zhou, Changyang; Hu, Xinde; Tang, Cheng; Liu, Wenjia; Wang, Shaoran; Zhou, Yingsi; Zhao, Qimeng; Bo, Qiyu; Shi, Linyu; Sun, Xiaodong; Zhou, Haibo; Yang, Hui
Summary: RNA-targeting CRISPR system Cas13 offers an efficient approach for manipulating RNA transcripts in vitro. In this perspective, we provide a proof-of-concept demonstration that Cas13-mediated Vegfa knockdown in vivo could prevent the development of laser-induced CNV in mouse model of Age-related macular degeneration.